2009
DOI: 10.1002/adfm.200901247
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐Crystalline Polymer with a Block Mesogenic Side Group: Photoinduced Manipulation of Nanophase‐Separated Structures

Abstract: In this report, a novel type of photoresponsive liquid crystalline polymer with a block mesogenic side‐group is demonstrated. The block mesogene is an amphipathic molecule containing a hydrophobic mesogene (azotolane moiety) and hydrophilic oligooxyethylene moieties in the same unit. The block mesogene in the polymer plays a role in liquid crystalline, amphiphilic and photoresponsive properties. As expected, a film prepared from the polymer exhibits phase separation of a lamellar structure due to cooperative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The Az polymer block in the cis‐ form probably provides the similar situation. Okano et al18 recently reported the erasure of nano‐morphology by UV light irradiation in a film of a homopolymer possessing Az and oligo(ethylene oxide) block in the side chain. Our observation involves the erasure of the MPS morphology originated from the main chain of the polymer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Az polymer block in the cis‐ form probably provides the similar situation. Okano et al18 recently reported the erasure of nano‐morphology by UV light irradiation in a film of a homopolymer possessing Az and oligo(ethylene oxide) block in the side chain. Our observation involves the erasure of the MPS morphology originated from the main chain of the polymer.…”
Section: Resultsmentioning
confidence: 99%
“… Okano et al18 recently reported the photoalignment of a stripe morphology for a thin film directing preferentially ‘parallel’ to LPL. The difference arises from the polymer architecture.…”
mentioning
confidence: 99%
“…In all these studies, BCPs were microphase-separated before illumination and light was used either to change the morphology, or to induce ordering or pattern different alignments of nanocylinders. [2][3][4][5][6] To the best of our knowledge, no photoinduced microphase separation in a BCP has been achieved thus far. Herein we report the first example.…”
Section: Introductionmentioning
confidence: 89%
“…Kadota et al [5] showed that the photoisomerization could change the morphology of a Langmuir-Blodgett monolayer film. Okano et al [6] synthesized a liquid crystalline polymer with an azo block mesogenic side group and showed that the photoisomerization could erase the lamellar morphology formed due to microphase-separated block side groups. In all these studies, BCPs were microphase-separated before illumination and light was used either to change the morphology, or to induce ordering or pattern different alignments of nanocylinders.…”
Section: Introductionmentioning
confidence: 99%
“…Another type of polymer architecture was reported by Okano et al They synthesized a series of LC homopolymers in which a “nanophase separation” occurs within the side chain (Table , 20 ). The side chains were composed of a hydrophobic azobenzene part and a hydrophilic oligo(ethylene oxide) part in the tail.…”
Section: Photocontrol and Alignment Of Microphase Separation In Blockmentioning
confidence: 99%